2006
DOI: 10.1097/01.mlr.0000218780.16064.df
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Intensive Care Unit Characteristics Affect the Incidence of Severe Intraventricular Hemorrhage

Abstract: The incidence of severe IVH is affected by NICU characteristics, suggesting important new strategies to reduce this important adverse outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
55
3
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 18 publications
4
55
3
7
Order By: Relevance
“…1,4,5,6,23,24,25,26 This study's mortality rates were similar to rates found in other institutions 27 . Though this study was carried out over a short period of time with a small sample size, our results suggest a reduction in overall mortality in non-NICU-TM hospitals (Table 2).…”
Section: Discussionsupporting
confidence: 70%
“…1,4,5,6,23,24,25,26 This study's mortality rates were similar to rates found in other institutions 27 . Though this study was carried out over a short period of time with a small sample size, our results suggest a reduction in overall mortality in non-NICU-TM hospitals (Table 2).…”
Section: Discussionsupporting
confidence: 70%
“…In addition to the association between high hospital level and decreased mortality of VLBWI [4][5][6], high patient volumes have been associated with decreased mortality [4,38] and rate of severe intraventricular haemorrhages (IVH) in VLBWI [39]. As shown in our previous study [5], VLBWI born in level III hospitals had lower 1-year mortality rates than those born in level II hospitals.…”
Section: Discussionmentioning
confidence: 76%
“…Foram feitos investimentos consideráveis na aquisição de equipamentos e na contratação de médicos e enfermeiros, e também foi dado início ao programa de regionalização do atendimento neonatal. Synnes et al demonstraram que a incidência de HPIV grave em 17 unidades neonatais canadenses não estava relacionada apenas às características dos recém-nascidos, mas também, e de modo importante, aos aspectos estruturais da organização das unidades, incluindo pessoal, relação do número de profissionais por leito e existência de serviços especializados 21 .…”
Section: Discussionunclassified
“…Tais práticas estão englobadas no que tem sido denominado como implementação de melhores práticas para prevenção de hemorragia cerebral e lesão cerebral isquêmica em recém-nascidos de muito baixo peso ao nascer [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] .…”
Section: Discussionunclassified